Mold Infections in Lung Transplant Recipients - Bhaskaran, Archana; Hosseini-Moghaddam, S.M; Rotstein, Coleman; Husain, Shahid (Seminars in Respiratory and Critical Care Medicine, 2013)
Fungal infections continue to produce morbidity and mortality in lung transplant recipients despite the widespread use of antifungal prophylaxis. There has been a decline in Candida infections but Aspergillus species predominate. Other mold pathogens including Fusarium, Scedosporium, and Zygomycetes also cause infections in lung transplant recipients. Furthermore, the widespread use of antifungal prophylaxis has prompted a delay in onset of Aspergillus infection in lung transplant recipients. Pulmonary parenchymal disease has become the most common manifestation of invasive aspergillosis. Among the risk factors pre- or posttransplant Aspergillus colonization is the most important risk factor reported in several retrospective studies. Recently posttransplant colonization has been implicated in the development of bronchiolitis obliterans syndrome. Other factors that have been reported include preceding cytomegalovirus infections, hypogammaglobulinemia, and single-lung transplantation. The risk factors for other mold infections such as Scedosporium, Fusarium, and Zygomycetes are not well studied. The best antimold prophylaxis strategy and choice of drug remains to be elucidated. Most lung transplant centers use either voriconazole or inhaled amphotericin preparations. However, data have emerged regarding the increased risk of squamous cell cancer in lung transplant recipients on voriconazole prophylaxis. Advances in the diagnosis and treatment of invasive aspergillosis have resulted in a significant decrease in mortality.
Keywords: lung transplantation; mold; prophylaxis; Aspergillus; Scedosporium; Fusarium; mucormycosis